Possession of Unlicensed Weapons in Comparative Laws - Hmood, Hussein; Abood, Samer (Journal of Legal Sciences, 2023)
The crime of possessing unlicensed weapons is considered a very dangerous crime for individuals and the entire state system، and possession of unlicensed weapons is the backbone of the existence of organized crime in society، given the serious consequences of this crime when used، which are loss of life and bodily injury to individuals، as well as On the psychological effects of fear، insecurity and loss of confidence in the security services. The study dealt with possession in criminal jurisprudence as well as in civil jurisprudence، and the definition of weapons and their types was also addressed، and we noticed through the research that sound and light weapons، unusable weapons and weapon parts are not considered a firearm and cannot be criminalized، as the weapon is mentioned in the law exclusively. It is not permissible to expand it.